Cashew nut (Anacardium occidentale L.) and cashew nut oil reduce cardiovascular risk factors in adults on weight-loss treatment: a randomized controlled three-arm trial (Brazilian Nuts Study) - Meneguelli, Talitha Silva; Kravchychyn, Ana Claudia Pelissari; Wendling, Aline Lage; Dionísio, Ana Paula; Bressan, Josefina; Martino, Hercia Stampini Duarte; Tako, Elad; Hermsdorff, Helen Hermana Miranda (Frontiers in Nutrition, 2024)
Introduction: Cashew nut contains bioactive compounds that modulate satiety and food intake, but its effects on body fat during energy restriction remains unknown. This study aimed to assess the effects of cashew nut and cashew nut oil on body fat (primary outcome) as well as adiposity, cardiometabolic and liver function markers (secondary outcomes). Materials and Methods: An eight-week (8-wk) randomized controlled-feeding study involved 68 adults with overweight/obesity (40 women, BMI: 33 ± 4 kg/m 2 ). Participants were randomly assigned to one of the energy-restricted (-500 kcal/d) groups: control (CT, free-nuts), cashew nut (CN, 30 g/d), or cashew nut oil (OL, 30 mL/d). Body weight, body composition, and blood collection were assessed at the baseline and endpoint of the study. Results: